Área de proteção e recuperação dos mananciais – Guarapiranga (APRM-G) sob ameaça: uma nova forma de produção ilícita de loteamentos irregulares no município de São Paulo - Victória Caroline Vidal (2024)
For many years, the presence of illegal subdivisions has been a critical issue in the Watershed Protection and Recovery Area – Guarapiranga (APRM-G). If irregularity in itself is already a serious social and environmental problem, now the challenges have reached a higher level with the alleged presence of sectors of so-called organized crime in the enterprise, which imposes new challenges on the State in facing the issue. The concern lies in the fact that organized crime has an organizational and structural apparatus that is considerably different from the modus operandi of irregular landowners, which we will call classics here. Considering this context, the objective of this work is to contribute to the understanding of Parallel Power, specifically the First Command of the Capital (PCC) in the production of irregular subdivisions and the circumstances that can elucidate the faction's interest in APRM-G, our object of study. To achieve the proposed objective, we carried out a search using secondary data in the available databases, namely dados Abertos and HabitaSampa, belonging, respectively, to the São Paulo City Hall and the Municipal Housing Secretariat (SEHAB). After this procedure, we requested some information and data from the Subprefectures of Capela do Socorro, M'boi Mirim and Parelheiros, as well as the Municipal Housing Secretariat (SEHAB), the Municipal Green and Environment Secretariat (SVMA) and the Police Military Environmental. Finally, we carried out a systematic review of the press, based on a descriptive approach to facts that occurred and reports published between 2007 and 2023. A new reality is being established in the region, if previously irregular subdivisions had as their target audience the social classes of low income, which did not have the means to obtain it through formal means, today, such enterprises, allegedly orchestrated by sectors of organized crime, also reach subjects belonging to the middle class. Precarious irregular subdivisions, typical of the past, are giving way to developments in the form of gated and well-structured condominiums in terms of water, sewage, lighting and paving services. In some of these condominiums, it is possible to find large residences with more than one floor and some houses even contain swimming pools, which contrasts with the precarious housing that predominated in such subdivisions in previous decades.